2002
DOI: 10.2139/ssrn.1817241
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Maritime Transport Costs

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“… A series of papers find that the elasticity of shipping costs to distance is around 0.2 (Radelet and Sachs, ; Fink et al ., ; Limão and Venables, ; Micco and Pérez, ; Clark et al ., ). However, the OECD () study uses the most comprehensive shipping costs dataset, and therefore our relatively high elasticity can be reconciled with the existing literature, because distance seems to matter more for shipping costs between East Asia and Europe. …”
mentioning
confidence: 99%
“… A series of papers find that the elasticity of shipping costs to distance is around 0.2 (Radelet and Sachs, ; Fink et al ., ; Limão and Venables, ; Micco and Pérez, ; Clark et al ., ). However, the OECD () study uses the most comprehensive shipping costs dataset, and therefore our relatively high elasticity can be reconciled with the existing literature, because distance seems to matter more for shipping costs between East Asia and Europe. …”
mentioning
confidence: 99%
“…When base rates are correlated with distance an inverse and statistically insignificant coefficient of À0.321is obtained. This goes against the findings of much recent research, where several authors using quantitative analysis (Wilmsmieir and Hoffman, 2008;Micco and Perez, 2002;Limao and Venables, 2001), conclude that distance is a determinant of freight rates since it is a surrogate for time at sea and thus influences variable costs such as labor and fuel. Our result supports the finding of a recent report (OECD, 2008) that criticized physical distance as a good determinant of trade and that relative distance might be more appropriate, especially time.…”
Section: Base Ratesmentioning
confidence: 63%
“…Therefore, distance was closely related to increased costs. Márquez-Ramos et al [47], Micco and Perez [48], and Wilmsmeier et al [49] revealed that a 1% increase in the distance per trip (the unit in kilometer) would result in a 0.25% increase in the freight costs. Although the tariff of the transportation services is mainly determined by supply and demand situations and conditions, a geographical distance undoubtedly affects the transportation costs.…”
Section: Recommendation For Future Logistics Costs Model In Indonesiamentioning
confidence: 99%